2020
DOI: 10.1161/circresaha.120.316704
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic and Transcriptomic Dynamics During Human Heart Organogenesis

Abstract: Rationale: There is growing evidence that common variants and rare sequence alterations in regulatory sequences can result in birth defects or predisposition to disease. Congenital heart defects (CHDs) are the most common birth defect and have a clear genetic component, yet only a third of cases can be attributed to structural variation in the genome or a mutation in a gene. The remaining unknown cases could be caused by alterations in regulatory sequences. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 115 publications
2
60
0
Order By: Relevance
“…Genetic variants at such non-coding regulatory sequences might influence the presentation of complex disorders by influencing chromatin accessibility, histone modifications, and downstream consequences of chromatin remodeling and gene expression (Table 3). Cardiac epigenomic maps have been generated for human and rodent hearts (Preissl et al, 2015;VanOudenhove et al, 2020), but only little is known about how specific histone modifications contribute to individual CHD phenotypes. Our understanding of epigenetic enhancer-promoter regulation of cardiogenesis has recently advanced with the development of genome-wide association studies (GWAS) and chromatin quantitative trait loci (chQTL; Box 1) analyses, elucidated by the epigenetic profiling of specific tissues, and by chromosome conformation capture (3C) and its derivatives (4C, Hi-C and HiChIP) that profile the spatial interaction of loci within and between chromosomes.…”
Section: Understanding Epigenetic Contributions To Chdmentioning
confidence: 99%
“…Genetic variants at such non-coding regulatory sequences might influence the presentation of complex disorders by influencing chromatin accessibility, histone modifications, and downstream consequences of chromatin remodeling and gene expression (Table 3). Cardiac epigenomic maps have been generated for human and rodent hearts (Preissl et al, 2015;VanOudenhove et al, 2020), but only little is known about how specific histone modifications contribute to individual CHD phenotypes. Our understanding of epigenetic enhancer-promoter regulation of cardiogenesis has recently advanced with the development of genome-wide association studies (GWAS) and chromatin quantitative trait loci (chQTL; Box 1) analyses, elucidated by the epigenetic profiling of specific tissues, and by chromosome conformation capture (3C) and its derivatives (4C, Hi-C and HiChIP) that profile the spatial interaction of loci within and between chromosomes.…”
Section: Understanding Epigenetic Contributions To Chdmentioning
confidence: 99%
“…(More putative variants were identified other than these five representative ones) Kapoor et al, 2019 This mode of gene regulation can recruit transcriptional machinery from cell-lineage genes in a process known as cofactor squelching (Schmidt et al, 2015(Schmidt et al, , 2016. Indeed a detailed knowledge of acute and chronic inflammatory enhancer biology during heart development and disease is essential and integrating this information with emerging compendiums of heart epigenomic data (such as Vanoudenhove et al, 2020) will be valuable. Integrating enhancer information into the functional annotation of non-coding variants is no doubt a powerful approach; however, it should be noted that disrupting enhancer activities is not the only mechanism underlying the pathological consequences of non-coding variants.…”
Section: Qt Interval Variationsmentioning
confidence: 99%
“…To study cardiac enhancer dynamics across multiple stages of in vitro cardiac differentiation or in vivo development, several studies from individual labs as well as consortiums, have utilized robust genome-wide assays that do not rely on mapping specific transcription factors, namely ChIP-seq for histone modifications ( Paige et al, 2012 ; Wamstad et al, 2012 ; Nord et al, 2013 ; Vanoudenhove et al, 2020 ), and DNase-seq and ATAC-seq for chromatin accessibility ( Bertero et al, 2019 ; Gorkin et al, 2020 ; Meuleman et al, 2020 ). These studies revealed highly dynamic chromatin states accompanying cardiac differentiation and development.…”
Section: Unmasking Heart Enhancers With Comparative and Functional Gementioning
confidence: 99%
See 2 more Smart Citations